2015
DOI: 10.1111/hepr.12539
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 24‐h soluble gelatin sponge particles and their effect on liver necrosis following hepatic artery embolization: Results of in vitro and in vivo studies

Abstract: HAE with 200-500-µm SGSP had greater effects on promoting liver necrosis without biliary damage than did HAE with 500-1000-µm SGSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…23 SGS was prepared from RMG by changing the temperature at which the cross-links are formed and by controlling the dissolution time in saline. 22,24 Takasaka et al reported that hepatic arteries were completely recanalized at 2 days after embolization using SGS (50 kDa, heat-induced cross-linking at 138 C) without the development of collateral pathways in swine. 23 Kawai et al reported that TACE using 2D-SGS had similar therapeutic effects and adverse effects to those of TACE using insoluble gelatin sponge particles while causing significantly less hepatic artery impairment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 SGS was prepared from RMG by changing the temperature at which the cross-links are formed and by controlling the dissolution time in saline. 22,24 Takasaka et al reported that hepatic arteries were completely recanalized at 2 days after embolization using SGS (50 kDa, heat-induced cross-linking at 138 C) without the development of collateral pathways in swine. 23 Kawai et al reported that TACE using 2D-SGS had similar therapeutic effects and adverse effects to those of TACE using insoluble gelatin sponge particles while causing significantly less hepatic artery impairment.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, we developed an RMG with extremely low endotoxicity and antigenicity 23 . SGS was prepared from RMG by changing the temperature at which the cross‐links are formed and by controlling the dissolution time in saline 22,24 . Takasaka et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation